Formation of sanogenic thinking as the way of avoiding obsessive thoughts - Gilman, Anna (Psychosomatic Medicine and General Practice, 2018)
This is a conference abstract from the 12th Scientific-Practical Conference of Students and Young Scientists "Medical Psychology 12.0: Aspects of Clinical Practice". It is dedicated to formation of sanogenic thinking as the way of avoiding obsessive thoughts.